2014
DOI: 10.1371/journal.pone.0098180
|View full text |Cite|
|
Sign up to set email alerts
|

Unacylated Ghrelin Suppresses Ghrelin-Induced Neuronal Activity in the Hypothalamus and Brainstem of Male Rats

Abstract: Ghrelin, the endogenous growth hormone secretagogue, has an important role in metabolic homeostasis. It exists in two major molecular forms: acylated (AG) and unacylated (UAG). Many studies suggest different roles for these two forms of ghrelin in energy balance regulation. In the present study, we compared the effects of acute intracerebroventricular administration of AG, UAG and their combination (AG+UAG) to young adult Wistar rats on food intake and central melanocortin system modulation. Although UAG did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 47 publications
1
19
0
2
Order By: Relevance
“…Future studies testing whether the putative DAG receptor and GHSR are co-localised at the ARC are critical for discriminating between these possibilities. The induction of c-Fos has been previously used to identify the neuronal targets of DAG (33,47). Two independent studies have shown that DAG increases c-Fos in the POMC or nesfatin-1 neurones of the ARC.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies testing whether the putative DAG receptor and GHSR are co-localised at the ARC are critical for discriminating between these possibilities. The induction of c-Fos has been previously used to identify the neuronal targets of DAG (33,47). Two independent studies have shown that DAG increases c-Fos in the POMC or nesfatin-1 neurones of the ARC.…”
Section: Discussionmentioning
confidence: 99%
“…There are two major molecular forms of ghrelin, acylated ghrelin and des‐acyl ghrelin. Recently it has been suggested that des‐acyl ghrelin counteracts the orexigenic effects of acylated ghrelin (Stevanovic et al, 2014). Ghrelin levels usually increase in response to fasting.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study [8] found that the increase in UAG during an exercise training program was associated with reduced body weight without reducing calorie intake. This prompted us to speculate that UnAG might induce body weight loss by regulating neuronal activity [52] in the hypothalamus and brainstem which controls energy homeostasis and body weight [50]. Yet, further investigation is required to examine this speculation.…”
Section: Unacylated Ghrelin Restored Impaired Insulin Signaling In DImentioning
confidence: 99%